2011
DOI: 10.1111/j.1365-2710.2011.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of landiolol hydrochloride, an ultra-short-acting beta 1-selective blocker, on supraventricular tachycardia, atrial fibrillation and flutter after pulmonary resection

Abstract: Continuous intravenous infusion of landiolol was found to be effective and safe for supraventricular tachycardia after pulmonary resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Landiolol is a highly adjustable β-blocker because it is administered intravenously and has a very short half-life of about four minutes. Nakano et al [11] also reported that continuous landiolol infusion is safe during open-heart surgery. In fact, none of the patients in Group L experienced severe hypotension or bradycardia that required discontinuation of landiolol therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Landiolol is a highly adjustable β-blocker because it is administered intravenously and has a very short half-life of about four minutes. Nakano et al [11] also reported that continuous landiolol infusion is safe during open-heart surgery. In fact, none of the patients in Group L experienced severe hypotension or bradycardia that required discontinuation of landiolol therapy.…”
Section: Discussionmentioning
confidence: 98%
“…A similar efficacy and good tolerance was revealed in two additional series of patients treated with landiolol. Control of heart rate was effective in 85% 29 and 92% 22 of patients. This was associated with a cardioversion to sinus rhythm in 56% (14/25) 29 and 77% (10/13).…”
Section: Landiolol Use To Control Heart Rate In Patients With Post-opmentioning
confidence: 96%
“…The landiolol dosages used in these series of patients were higher, applying loading dose of 60 mcg/kg/min followed by infusion of 10 mcg/kg/min titrated upwards to 40 mcg/kg/min 22 , 29 …”
Section: Landiolol Use To Control Heart Rate In Patients With Post-opmentioning
confidence: 99%
See 1 more Smart Citation
“…Landiolol has also been shown to be well tolerated in the critically ill for its limited negative inotropic effect and minimal impact on blood pressure [99][100][101]. The use of low doses (5-10 mcg kg -1 min -1 ) of landiolol is usually sufficient for the cardioversion of AF compared to controls.…”
Section: Beta-blockersmentioning
confidence: 99%